The Role of Developmental loans in Developing Wheat and Barley Crops In Iraq for the Period ( 2006 – 2012) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The present paper attempts to find out the role of developmental loans in promoting strategic crops especially the basis stemming from the problem of non - defining economic feasibility study and the negative or positive revenues of developmental loans, directed to Iraqi Agricultural sector in general and Basic strategic crops in particular which resulted in the difficulty of planning and future prediction to grant loans agriculturally directed in terms of quality and quantity and the arbitrary of distributing these loans .the strategic crops have been selected as sample of population where the sample of Basic strategic crops include wheat and barley .The paper has come to several of conclusions mainly are as follows :- the increase in number and amounts of developmental loans continuously represented by count up leap especially via the final help of duration of the research which signals the increase in governmental development support during this period .Secondly , the concerned entities are unable to conduet and manage the file of developmental loans granted strategic crops in general and barely in particular in spite of the great support for this file .In addition to the increase of financial and numerical support of loans granted to the Iraqi agricultural sector - accordingly there are some recommendation that have been draw up out of this research : firstly , stablising the level of financial and numerical support of developmental loans granteed to agricultural sector and taking advantage of money amounts of paying off instalments of developmental loans by recycling them and granting them to the loans related to strategic crops .It is also important to take in to consideration not to increase the average of the amount of the loan and investing the available amounts to open new out lets for developmental loans of strategic crops . it is also important to set down general control and committees to follow up to ensure achieving loans aims and draw up peasibility study based on systematic and scientific bases